Inhibition of Bruton's tyrosine kinase regulates macrophage NF-κB and NLRP3 inflammasome activation in metabolic inflammation - Purvis, GSD; Collino, M; Aranda-Tavio, H; Chiazza, F; O'Riordan, CE; Zeboudj, L; Mohammad, S; Collotta, D; Verta, R; Guisot, NES; Bunyard, P; Yaqoob, MM; et al. (Wiley, 2020)
Background and Purpose Currently there are limited medicines available for the treatment of metabolic inflammation in diseases such as obesity and type 2 diabetes (T2D). Although initially associated with B‐ells, Bruton's tyrosine kinase (BTK) is present in a wide variety of cells including monocytes and macrophages, and has been implicated in the regulation of the NF‐κB and NLRP3 inflammasome activity. Experimental Approach Using in vivo models of chronic inflammation [high‐fat‐diet (HFD) feeding] and in vitro assays in primary murine and human macrophages we investigated if ibrutinib, an FDA approved medicine that targets BTK, may represent a novel anti‐inflammatory drug for the use in treating metabolic inflammation. Key results HFD feeding was associated with increased BTK expression and activation, which was significantly correlated with monocyte/macrophage accumulation in the liver, adipose tissue and kidney. Treatment of mice fed HFD with ibrutinib inhibited the activation of BTK and reduced monocyte/macrophage recruitment to the liver, adipose tissue and kidney. Reduced inflammatory gene expression associated with decreased activation of NF‐κB and the NLRP3 inflammasome in vivo. As a result, ibrutinib treated mice fed HFD had improved glycaemic control through restored signalling by the IRS‐1/Akt/GSK‐3β pathway; protecting mice against the development of hepatosteatosis and proteinuria. We show that inhibition of BTK reduces activation of NF‐κB and the NLRP3 inflammasome specifically in primary murine and human macrophages; which are the primary target of ibrutinib in vivo in the setting of metabolic inflammation. Conclusions and Implications In the present study we provide ‘proof of concept' evidence that BTK is a novel therapeutic target for the treatment of diet ‐metabolic inflammation. Ibrutinib may be a candidate for drug repurposing as an anti‐inflammatory for the treatment of metabolic inflammation in T2D and microvascular disease.